INTERFERENCE. ITS MMEANING CONTENT AND THEIR ELIMINATION IN TWO CONTACTING LANGUAGES - Kenjaboyev SH. A (International Engineering Journal For Research & Development, 2021)
This article deals with the types of interference in the two contacting languages- English and Uzbek. The elimination of the interferences.